Water Status Evaluation on Tertiary Block for Developing Land Use Pattern and Water Management Strategies in Acid Sulfat Soil of Saleh Tidal Lowland Reclamation Areas of South Sumatera - Momon Sodik Imanudin; M.E. Armanto; R.H. Susanto; S.T. Bernas (AGRIVITA, Journal of Agricultural Science, 2010)
The aimed of the research is to evaluate the water status in the tertiary block of tidal lowland for developing cropping pattern and water management strategies for food crop agriculture. The research was conducted in tidal lowland reclamation areas of Delta Saleh South Sumatera. The methodology used this research was survey and monitoring. Data analysis was done by comparing the water status availability with the potential cropping pattern. Computer model of DRAINMOD had been used to estimate the water table status and to design water table control operation at tertiary blocks. Model adaptation for dry land condition (C-typhology) showed that the best scenario was land utilization pattern of rice-corn. This paper presented monthly water management operational plan for rice crop in first cropping season (MT1) during November-February period and for corn crop in second cropping season (MT2) during May-August period. Keywords: Water status, Tidal lowland, acid sulfate soil, Surplus Excess Water (SEW-30) cm